The attitudes of medical students towards rare diseases: A cross-sectional study - Medić Branislava; Divac Nevena; Stopić Bojan; Savić-Vujović Katarina; Glišić Andreja; Cerovac Nataša; Stojanović Radan; Srebro Dragana; Prostran Milica (Vojnosanitetski Pregled)
Background/Aim. Rare diseases are chronic, degenerative and may lead to permanent disability. We aimed to assess knowledge and attitudes of the 3rd and 6th year medical students towards the treatment of rare diseases in Serbia. Methods. In this cross-sectional study, two samples of students were questioned for a survey: 350/446 (78.48%) students of the 3rd year, and 242/517 (46.81%) students of the 6th year. Results. Sixth year students estimated that they were more informed on the issue analyzed than the 3rd year students (median value of 4 and 3, interquartile range of 3-5, and 1-4, respectively; p < 0.05). However, a significant percentage of participants estimated incorrectly the prevalence of rare diseases according to the European Union standards (3rd year - 42.68%, 6th year - 49.55%). Core curriculum subjects were the main source of information on rare diseases (3rd year - 63.14%; 6th year - 92.14%). Our participants agreed that the most important problems are the following: high drug prices, difficult access to drugs and lack of public information. Students found, without any differences, that community access to effective drugs for rare disease should be improved (median value - 10, interquartile range 8-10 in both groups, p < 0.05). In order to improve pharmacotherapy of rare diseases in Serbia, the participants suggested establishment of a National Plan for Rare Diseases, approval of more appropriate drugs, simplified access to appropriate medicines, and more rapid diagnostics. Conclusion. It is necessary to improve the knowledge and attitudes of medical students towards pharmacotherapy of rare diseases. [Projekat Ministarstva nauke Republike Srbije, br. 175023]